Influence of burn severity on endothelial glycocalyx shedding following thermal trauma: A prospective observational study. Issue 3 (May 2021) - Tapking, C.; Hernekamp, J.F.; Horter, J.; Kneser, U.; Haug, V.; Vogelpohl, J.; Schulte, M.; Kremer, T.; Hundeshagen, G.
Highlights: There are moderate correlations between burn size and levels of syndecan and heparansulfate Correlations between administered fluid volume and levels of syndecan and heparansulfate were shown Levels of glycocalyx metabolites can not be used for prediction of clinical outcomes following burns Abstract: Objective: Severe burns cause hypermetabolic and inflammatory responses are treated with significant volume resuscitation. This study aimed to evaluate correlations between glycocalyx metabolites and the burn size as well as certain clinical parameters such as administered fluid volumes. Study design: Severely burned patients with a total body surface area (TBSA) burned smaller and larger than 20% were included. Clinical parameters including length of stay, mortality, fluid administration and Sequential Organ Failure Assessment (SOFA) score as well as syndecan and heparansulfate, as laboratory parameters for endothelial damage, were obtained. Results: A total of 39 patients (32 males, 7 females) with a mean age at burn of 45 ± 21 years were included. Syndecan levels decreased and heparansulfate levels increased over time. In both heparansulfate and syndecan, there was no significant difference between burns smaller and larger than 20% TBSA at any time point. Syndecan levels at 24 h after burn correlated significantly with IL-10 levels at admission (R = 0.58 and p < 0.05). There were significant linear correlations of %TBSA and cumulative administration of fluids after 24 h on syndecan levels after 48 h. Correlations between clinical parameters and syndecan or heparansulfate levels over time were not found. Conclusions: This study shows that even though there are moderate correlations with burn size and administered fluid volume, levels of syndecan and heparansulfate are not predictive for clinical outcomes of burned patients in our cohort. Further studies with higher numbers evaluating the effect of large burns on glycocalyx shedding over a longer period of time are needed. Showing significant glycocalyx shedding in large burn including potentially correlations with clinical outcomes may yield new therapeutic targets.